Long-Term Performance Comparison of Bipolar Active vs. Quadripolar Passive Fixation Leads in Cardiac Resynchronisation Therapy - Schiedat, Fabian; Bogossian, Harilaos; Schöne, Dominik; Aweimer, Assem; Patsalis, Polykarpos C.; Hanefeld, Christoph; Mügge, Andreas; Kloppe, Axel (Frontiers in Cardiovascular Medicine, 2021)
Background: Bipolar active fixation (BipolarAFL) and quadripolar passive fixation left-ventricular leads (QuadPFL) have been designed to reduce risk of phrenic nerve stimulation (PNS), enable targeted left-ventricular pacing as well as overcome problems of difficult coronary venous anatomy and lead dislodgment. This study sought to report long-term safety and performance of a BipolarAFL, Medtronic Attain StabilityTM 20066, compared to QuadPFL. Methods: We performed a single-centre retrospective analysis of 81 patients receiving CRT (36 BipolarAFL, 45 QuadPFL). Immediate implant data as well as electrical and clinical data during follow-up (FU) were analysed. Results: BipolarAFL has been chosen in patients with significantly larger estimated vein diameter (at lead tip: 7.2 ± 4.1 Fr vs. 4.1 ± 2.3 Fr, p<0.001) without significant time difference until final lead position was achieved (BipolarAFL: 20.9 min, IQR 8 – 34 vs. QuadPFL:18.9 min, IQR 6 – 32, p = 0.35). At 12 month FU no difference in response rate to CRT was recorded between BipolarAFL and QuadPFL according to LVESV (61.1 % vs. 60.0%, p = 0.82) and NYHA (66.7% vs. 62.2%, p = 0.32). At mean FU of 48 months (IQR: 44 – 54) no lead dislodgment occurred in both groups but a significantly higher proportion of PNS was recorded in QuadPFL (13% vs. 0%, p<0.05). Electrical parameter were stable during FU in both groups without significant differences. Conclusion: BipolarAFL can be implanted with ease in challenging coronary venous anatomy, significantly reduces PNS, shows excellent electrical performance, is safe and has non-inferior clinical outcome compared to QuadPFL.